Fricatives, affricates and vowels in Croatian children with cochlear implants - Mildner, Vesna (Array, 2006)
The aim of the research was to analyze the speech of the children with cochlear implants over approximately a 40-month period, and compare it with the speech of hearing controls. We focused on three categories of sounds in Croatian: vowels, fricatives and affricates, that have been shown to differ between the cochlear implant users and unimpaired children. The following variables were analyzed: vowels (F1 and F2), fricatives /s/ and /∫ / (spectral differences), and affricates /ts/ and /t∫ / (total duration and pattern of stop-fricative components). One group of subjects were implanted children (N = 12). There were four recordings per child. All 12 children had been profoundly deaf before implantation. Their age ranged from 13 ; 10 to 17 years. Age at implantation ranged between 4 and 12 years. Group two were hearing controls matched for age and sex. Hearing impaired children were involved in hearing and speech therapy at the SUVAG Polyclinic in Zagreb, Croatia. Controls were students of public schools in Zagreb. Acoustic analyses were carried out using Praat software. The results show that the implanted children are closest to unimpaired children in terms of their formant-defined vowel space. Their fricatives exhibit with poor distinction in terms of the noise spectrum and the affricates are the most difficult.